Analysis of the siting procedure for radioactive waste management facilty in Korea - Wee, Sun-Mi (KDI School, 2012)
With the world struggling due to a lack of sufficient energy, nuclear power has become an indispensable power source. The need for safe management of nuclear related facilities has increased in unison with an increased use of nuclear energy. The effective management of radioactive waste has become a significant national issue in Korea. Korea had struggled to select an appropriate site for its radioactive waste management facility and ever since 1986, there have been many conflicts and concerns regarding safety and reliability of the facility. After much deliberation, the Korean government finally selected the Gyeongju repository site by way of referendum in November, 2005. This study analyzes the key factors and procedures which resulted in the selection of Gyeongju as the waste management site as well as major differences between this location and the other unsuccessful options. This study examines whether or not the referendum is useful with regards to radioactive waste site selection and in which ways it can be differentiated from other procedures pertaining to the site’s selection. This study will cover many issues, including 1) the way that Korea selected the radioactive waste facility in Gyeongju ? how the path of selection process has changed 2) the history of and common factors dictating site selection processes in other countries, 3) lessons learned from the Gyeongju case and how these lessons can be developed for future implementation. The Gyeongju case is analyzed by the point of periodical changes, and changes in approach. There are a certain characteristic aspects of approach ? change of compensation, diversification of deliberation structure, and enlargement of local people participation. Despite a great deal of effort on their part, Korea failed on several occasions to select a suitable site, but reached a turning point following the introduction of the referendum, with public receptivity changing dramatically. In addition to analyzing the Korean case, this study also analyzes the experiences of countries like Canada, United Kingdom, and France, who have also encountered similar obstacles when attempting to settle on a site location for radioactive waste management facilities. Indeed, thorough periodic research demonstrates the approach taken by these countries and assesses the success of these approaches. In conclusion, policy acceptance level is determined on the base of trust between residents and policy executors, whilst decision a making process should have openness and transparency. With this in mind, the policy makers should attempt to enhance community participation in all phases of the siting process by showing their support for independent consultants, community review of facility design and safety systems, monitoring of facility performance and property value protection.
Thesis(Master) --KDI School:Master of Public Policy,2012